STUDI KORELASI KECENDRUNGAN BERPIKIR DIVERGEN DAN KONVERGEN DENGAN HASIL BELAJAR KIMIA SISWA KELAS X MAN 2 MATARAM TAHUN PELAJARAN 2012/2013 - NURSA’BAN, EVA (IKIP Mataram, 2013)
Chemical material contains concepts of formulas that must be completed by the students. The purpose of this research is to know: (1) correlation of divergent thinking character with achievement of chemistry learning of class X MAN 2 Mataram academic year 2012/2013; (2) correlation of convergent thinking characters with chemistry learning outcomes. This type of research is correlational. The subjects of the study were 166 students of class X. Data thinking characters are collected using questionnaires of divergent / convergent thinking characters. Learning result data is obtained at the end of semester. Data analysis used is Pearson product moment correlation. The results show that there is a negative correlation between diverging thinking characters and learning outcomes. This means that the higher the tendency of divergent thinking of the students, the lower the learning result, this is proved by the value of r-test (-0.121) <-r-tabel (-0,044). In addition, convergent thinking characters are positively correlated between convergent thinking characters and learning outcomes. This means that the higher the tendency of convergent students thinking, then the learning result will be high, this is proved by the value of r-test (0.048)> r-table (0.044). We conclude that: (1) the divergent thinking character of the students is negatively correlated with the learning outcomes; (2) the convergent thinking characters in the students are positively correlated with the learning outcomes.